The mediating role of career decision self-efficacy on the relationship of career emotional intelligence and self-esteem with career adaptability among university students - Hamzah, Siti Raba’ah; Khoo, Kai Le; Musa, Siti Nur Syuhada (Routledge, 2021)
This study was undertaken to investigate whether career decision self-efficacy (CDSE) could mediate the relationships of career adaptability with emotional intelligence and with self-esteem among university students. Using cluster random sampling, a total of 205 university students aged 22 to 24 years (M age = 23.0, SD = .875) were selected as respondents. The strongest linear relationship was found between CDSE and career adaptability (r = .568, p = .001). Besides CDSE the main predictor of career adaptability (β = .354, p = .000), emotional intelligence (β = .282, p = .000) and self-esteem (β = .145, p = .019) also contributed significantly to career adaptability. CDSE was found to significantly mediate the influences of emotional intelligence and self-esteem on career adaptability. These results suggest that undergraduate students’ emotional intelligence, self-esteem and CDSE are substantially associated with career adaptability, which plays an important role in workforce efficiency and graduates’ employability.